Study on the dual inhibition behavior of interfacial IMCs in Cu/SAC105/Cu joint by adopting SiC nanowires and nanocrystalline Cu substrate - Xiao Lu; Liang Zhang; Yong-huan Guo; Li-Yin Gao; Xi Wang; Chen Chen; Zhi-Quan Liu (Journal of Materials Research and Technology, 2023)
To obtain high-strength joints suitable for three-dimensional (3D) packaging, SiC nanowires (NWs) were doped to the Sn1.0Ag0.5Cu (SAC105) solder, and the conventional Cu substrate was replaced with nanocrystalline (NC) Cu to form Cu/solder/NC Cu solder joints. It was found that the application of SiC NWs and NC Cu had an essential effect on the evolution and growth kinetics of the solder joint interface. The formation of intermetallic compounds (IMC) bridging and full-IMC joints at the interface was delayed. The absorption effect of SiC NWs and numerous nucleation sites provided by NC Cu resulted in a notable reduction in interfacial IMC grains size and interfacial Cu3Sn IMC layer thickness. In addition, the Cu/SAC105-SiC/NC Cu solder joint exhibited the highest shear strength. On the one hand, SiC NWs were incorporated into Cu6Sn5 IMC grains to form the reinforced concrete structure. On the other hand, NC Cu provided more fine Cu6Sn5 IMC grains for the interface. Combined with the analysis of the fracture morphology, it can be concluded that the combination of SiC NWs and NC Cu substrate substantially improved the mechanical properties of the solder joints.